Plasmid-Mediated Quinolone Resistance in Shigella flexneri Isolated From Macaques - Mannion, Anthony J.; Martin, Heather R.; Shen, Zeli; Buckley, Ellen M.; Dzink-Fox, JoAnn L.; Garcia, Alexis; Marini, Robert P.; Patterson, Mary M.; Fox, James G. (Frontiers in Microbiology, 2018)
Non-human primates for biomedical research are commonly infected with Shigella spp. that can cause acute dysentery or chronic episodic diarrhea. These animals are often prophylactically and clinically treated with quinolone antibiotics to eradicate these possible infections. However, chromosomally- and plasmid-mediated antibiotic resistance has become an emerging concern for species in the family Enterobacteriaceae. In this study, five individual isolates of multi-drug resistant Shigella flexneri were isolated from the feces of three macaques. Antibiotic susceptibility testing confirmed resistance or decreased susceptibility to ampicillin, amoxicillin-clavulanic acid, cephalosporins, gentamicin, tetracycline, ciprofloxacin, enrofloxacin, levofloxacin, and nalidixic acid. S. flexneri isolates were susceptible to trimethoprim-sulfamethoxazole, and this drug was used to eradicate infection in two of the macaques. Plasmid DNA from all isolates was positive for the plasmid-encoded quinolone resistance gene qnrS, but not qnrA and qnrB. Conjugation and transformation of plasmid DNA from several S. flexneri isolates into antibiotic-susceptible Escherichia coli strains conferred the recipients with resistance or decreased susceptibility to quinolones and beta-lactams. Genome sequencing of two representative S. flexneri isolates identified the qnrS gene on a plasmid-like contig. These contigs showed >99% homology to plasmid sequences previously characterized from quinolone-resistant Shigella flexneri 2a and Salmonella enterica strains. Other antibiotic resistance genes and virulence factor genes were also identified in chromosome and plasmid sequences in these genomes. The findings from this study indicate macaques harbor pathogenic S. flexneri strains with chromosomally- and plasmid-encoded antibiotic resistance genes. To our knowledge, this is the first report of plasmid-mediated quinolone resistance in S. flexneri isolated from non-human primates and warrants isolation and antibiotic testing of enteric pathogens before treating macaques with quinolones prophylactically or therapeutically.